The growing crisis in private equity: binding regulation and an action plan are needed - Vitols, Sigurt (Brussels, 2009)
"There is a storm brewing in private equity as the economic crisis raises the threat of bankruptcy or default over perhaps as many as one in two firms acquired by PE funds. This poses a major additional threat to the already weakened banking sector. Two sets of policy issues emerge. First, regulation is needed to improve transparency, discourage destructive financing and industrial relations practices, and support worker rights to information, consultation and negotiation. An independent European rating agency is also needed to monitor PE investments. Second, in order to protect employment at PE-financed companies from the threat of increasing default on LBO debt, an action plan is urgently needed to secure refinancing for PE portfolio companies. This action plan will need the support of governments, institutional investors, the PE industry and trade unions."